Emotional exhaustion in university students within the health field - Barreto-Osama, Doris; Salazar-Blanco, Henry Augusto (Universidad y Salud, 2020)
Introduction: Emotional exhaustion (EE) is a state of emotional and physical burnout and energy depletion that are associated with feelings of frustration and failure. University students experience situations that combine various stressful elements. Objective: To describe EE health field students from universities of the city of Bucaramanga – Colombia. Materials and methods: A qualitative study with a flexible, descriptive and interpretative design was carried out, which included 175 open interviews conducted in a consensual and voluntary manner. Results: Three categories and respective subcategories were revealed: (i) emotional exhaustion (physiological and psychological consequences); (ii) associated difficulties (academic, social and familiar); and (iii) coping strategies (active and decisive or passive and negative). Conclusions: Students experience EE, which affects their physical and mental health, decreases their academic performance and disturbs their familiar and social interactions. Some students apply decisive coping strategies, while others use negative ones. EE can be mitigated through prevention strategies and psychosocial support.